The Use of Gravitational Lenses in the Study of Distant Galaxy Mergers - Kats, A.V.; Kontorovich, V.M. (Радиофизика и радиоастрономия, 2013)
The paper is based on the report at the conference EMES-2012 dedicated to P. V. Bliokh, one of the pioneers in the study of gravitational lenses. We discuss a vivid example of observation of the galaxy merger at a redshift close to z= 3 using gravitational lensing (by Boris, et al. and Berciano Alba, et al.). In connection with observation of the galaxy luminosity function evolution in the Hubble ultra deep field (Bouwence, et al.), a description of the mass function slope evolution due to minor mergers is proposed, which satisfactorily describes the results of observations.